2022
DOI: 10.1007/s00417-022-05830-3
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype, genotype, and management of congenital fibrosis of extraocular muscles type 1 in 16 Chinese families

Abstract: Purpose Congenital fibrosis of extraocular muscles type 1 (CFEOM1), a classical subtype of CFEOM, is characterized by restrictive ophthalmoplegia and ptosis. It is mainly caused by aberrant neural innervation of the extraocular muscles. This study aimed to investigate the genetic characteristics and clinical manifestations of CFEOM1 in Chinese families. Methods The clinical data, including ocular examinations, magnetic resonance imaging (MRI), and surgical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Human KIF21A variants Below, we review the phenotypes reported with specific KIF21A variants, as summarized in Figure 5 and Table 4. (Yamada et al, 2003(Yamada et al, , 2004(Yamada et al, , 2005Chan et al, 2007;Lu et al, 2008;Yang et al, 2010;Wang et al, 2011;Al-Haddad et al, 2021;Moon et al, 2021;Jia et al, 2022;Chen et al, 2023). These heterozygous missense variants in KIF21A occur in association with CFEOM and were first reported in 2003 (Yamada et al, 2003).…”
Section: Tubb3 Can Influence Wildtype Microtubule Protofilament Numbermentioning
confidence: 99%
“…Human KIF21A variants Below, we review the phenotypes reported with specific KIF21A variants, as summarized in Figure 5 and Table 4. (Yamada et al, 2003(Yamada et al, , 2004(Yamada et al, , 2005Chan et al, 2007;Lu et al, 2008;Yang et al, 2010;Wang et al, 2011;Al-Haddad et al, 2021;Moon et al, 2021;Jia et al, 2022;Chen et al, 2023). These heterozygous missense variants in KIF21A occur in association with CFEOM and were first reported in 2003 (Yamada et al, 2003).…”
Section: Tubb3 Can Influence Wildtype Microtubule Protofilament Numbermentioning
confidence: 99%